Maritime technology and engineering proceedings of MARTECH 2014, 2nd International Conference on Maritime Technology and Engineering, Lisbon, Portugal, 15-17 October 2014 - Soares, C. Guedes; Santos, T. A. (Balkema Book, 2015)
Maritime Technology and Engineering includes the papers presented at the 2nd International Conference on Maritime Technology and Engineering (MARTECH 2014, Lisbon, Portugal, 15-17 October 2014)